Catalogue of books printed before 1601 in the legal historical section of the Biblioteca di Scienze Sociali dell'Università degli Studi di Firenze - Douglas J., Osler (Firenze University Press, 2005)
The present catalogue seeks to provide a comprehensive record of the 1,532 editions printed in the 15th and 16th centuries held in the legal historical section of the Biblioteca di Scienze Sociali of the Università degli Studi di Firenze. This library is the successor to that of the Facoltà di Giurisprudenza, the nucleus of which remains the historic collection of the Collegio degli Avvocati di Firenze acquired in 1924. Supplemented by further important acquisitions, including the library of the Corte di Appello di Firenze, the collection has come to be numbered among the foremost in its fi eld in Italy. It exhibits a wide range not only of the famous medieval authors of the ius commune, but also of the growing number of contemporary 16th century jurists.